Plan de negocio para la elaboración, venta y distribución de cakes endulzados con stevia, en empaques de 60 gr. Para la ciudad de Quito - Proaño Vivanco, Carlos Alberto (2012)
This business plan aims to create a joint development and marketing of cakes (cake slices in packages of 60 gr. In the Metropolitan District of Quito, in order to generate jobs and make a trade by investment of funds. The business plan began to research and analysis of the environment, social variables, economic, political and technological also presented a study of the five competitive forces by Michael Porter. Then was performed market study, in which it was collected, processed and analyzed the data, identifying potential customers and consumers, competition that exists today, and concluded that there is a market opportunity. Having identified the business opportunity established a marketing plan with strategies according to the environment and the product that the company offers. Was created corporate structure, detailing the legal guidelines, duties and functions of personnel required to operate the project. And we defined a preoperational activity schedule, identifying the activities to be performed to put the going concern in order to predict and minimize the risks and challenges assumptions. Assumptions were established for the financial evaluation of business plan with projections for five years in three economic scenarios, optimistic, expected and pessimistic in two stages, with leverage and without leverage. Thefollowingresults: The study found that financial profitability. And thus concludes that the project is feasible in execution and implementation.